Diabetic Cardiovascular Autonomic Neuropathy: An Approach towards Insulin Resistance, Lipids and Simvastatin - Victoria A. Serhiyenko; Marta E. Hotsko; Samir Ajmi; Alexandr A. Serhiyenko (Issues and Developments in Medicine and Medical Research Vol. 10, 2022)
Treatment of diabetic cardiovascular autonomic neuropathy (CAN) is a complex process, that includes: Lifestyle modification; reducing of insulin resistance (IR); optimal glycemic control; management of diabetic dyslipidemia; antioxidants; vitamins; treatment of myocardial metabolic abnormalities; thrombosis and others. The aim of study was to investigate the effects of simvastatin on insulin resistance and blood lipid profile parameters in patients with type 2 diabetes mellitus (DM) and the definite stage of CAN. The study involved 107 patients with type 2 DM among them 16 patients without CAN, 19 with subclinical stage of CAN and 72 with definite CAN. Median age of patients was 53.6 ± 0.41 yrs, disease duration - 4.12 ± 0.24 yrs and median glycated hemoglobin (HbA1c) - 7.01% ± 0.09%. The control group included 14 almost healthy people without DM. Patients with definite CAN were allocated into two treatment groups: 1st group - 22 patients received standard hypoglycemic therapy and simvastatin 20 mg/day; 2nd group - control (n = 15). The duration of the study was 3 mos. The concentrations of glucose, HbA1c, immunoreactive insulin (IRI) in the blood were determined. Lipid metabolism was assessed by the concentration of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglycerides (TG) measurements. The IR index (HOMA-IR), atherogenic coefficient (AC), TG/HDL-C parameters, and TG-glucose (TyG) index were calculated. It was established that in patients with type 2 DM with subclinical stage of CAN there was statistically significant increase in the parameters of HbA1c, IRI, TC, TG and HOMA-IR, AC, TyG indices and decrease of TG/HDL-C and HDL-C compared to control; increase of IRI, TG, TG/HDL-C and TyG indices compared to patients with type 2 DM without CAN. The most pronounced atherogenic changes observed among patients with definite stage of cardiovascular autonomic neuropathy. The definite stage of CAN is characterized by an increase of HbA1c, IRI, TC, LDL-C levels and HOMA-IR, AC indices and a significant decrease in the concentration of HDL-C (compared to patients with subclinical CAN). As a result of our study, we found out that prescription of simvastatin to patients with definite stage of CAN was accompanied by a statistically significant decrease in the concentration of TC, LDL-C, TG and an increase in the content of HDL-C (compared to 2nd, control group). Obtained results justify the appropriateness of statins prescription to patients with type 2 DM and the definite stage of CAN.